Palermo’s Promise: Victims’ rights and human trafficking - Vandenberg, Martina E (Anti-Trafficking Review, 2016)
Response to ATR Debate Proposition: ‘Prosecuting trafficking deflects attention from much more important responses and is anyway a waste of time and money’